EDUMARA: (Edukasi Desa Ko’mara) Program Pemberdayaan Masyarakat Berbasis Sudut Eduliteraksi Sebagai Upaya Akselerasi Sdgs Desa Ko’mara Takalar - Syamsurijal, Syamsurijal; Riswansyah; Anastasya Zhera; Risaldi; Mujahidah (Jurusan Pendidikan Guru Sekolah Dasar Kampus VI Bone, 2025)
The low literacy rate and high school dropout rate in Ko'mara Village, Takalar Regency, are caused by limited access to education and family economic priorities that emphasize child labor over formal education. The EDULITERAKSI Corner Program was implemented as a comprehensive solution through the establishment of six literacy corners based on community needs, including child literacy, parenting, religious education, entrepreneurship, health, and women's empowerment. The implementation method adopted a Participatory Action Research approach that involved the community as active subjects in problem identification and solution implementation. The program lasted five months, involving 218 participants and forming 36 local literacy cadres through Training of Trainers. Success measurement used a mixed-method with pre-post test instruments, structured observation, and in-depth interviews. Results showed significant improvements across all indicators: basic literacy (35.3%), parenting understanding (42.6%), Qur'anic reading ability (35.3%), entrepreneurial skills (44.5%), health knowledge (43.4%), and digital literacy (45.1%). The program successfully established a formal literacy cadre institution with juridical legitimacy and produced SO'RI dodol economic products with a turnover of IDR 1,2 million in two months. In conclusion, a participatory approach based on community needs proves effective in improving literacy and economic empowerment of rural communities sustainably.